Periodontitis Home Screening with Mouth Rinse Cut-Off 20 Ng/mL aMMP-8 Test and Mobile Application - Miika Penttala; Timo Sorsa; Julie Toby Thomas; Andreas Grigoriadis; Dimitra Sakellari; Shipra Gupta; Pirjo Pärnänen; Tommi Pätilä; Ismo T. Räisänen (Diagnostics)
Background: In this study, we describe a method by which a patient can independently assess their own periodontitis risk, for example, at home, with a mobile application. The aim of the study is to use active matrix metalloproteinase aMMP-8 mouth rinse cut-off 20 ng/mL point-of-care testing (POCT) and a polynomial function to reveal patients’ statistical risk of periodontitis. Methods: The polynomial function presented in this study was modeled with multiple logistic regression and the function estimates the risk of periodontitis using a probability measure. To investigate variables associated with periodontitis, we used data from adult patients visiting dental clinics in Thessaloniki, Greece. Results: The research results revealed that with appropriate information it is possible to obtain sufficient accuracy about a patient’s potential risk of periodontitis. The function for estimating risk of periodontitis is PERIORISK = (1 + e−(3.392×X1+0.002×X2+1.858×X3−9.151))−1, where X1 = aMMP-8 test result and tobacco smoking status, X2 = age × waist circumference and X3 = patient’s individual and parental history of diabetes. Conclusions: The prediction of periodontitis risk using an aMMP-8 test and a polynomial function seems to be a useful, non-invasive, safe-to-use and cost-effective tool for all people. Overall, in the model created, mouth rinse cut-off 20 ng/mL aMMP-8 test result, age, waist circumference, tobacco smoking status and patient’s individual and parental history of diabetes were found to be good factors explaining the risk of periodontitis.